Hydrogel Particles: Super‐Soft Hydrogel Particles with Tunable Elasticity in a Microfluidic Blood Capillary Model (Adv. Mater. 43/2014). (November 2014) - Cui, Jiwei; Björnmalm, Mattias; Liang, Kang; Xu, Chenglong; Best, James P.; Zhang, Xuehua; Caruso, Frank
<x xml:space="preserve">Abstract</x> On page 7295, F. Caruso and co‐workers report a mesoporous silica templating method for preparing super‐soft PEG particles. The elasticity of the particles can be tuned to mimic the deformability behaviour of human red blood cells in a microfluidic blood‐capillary model. These particles provide a new platform for investigating bio‐nano interactions. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>